The Phenomenon of Disparity in a Criminal Case - Budi Wijaya Hamdi (Riviera Publishing, 2024)
The phenomenon of disparities in criminal cases is increasingly common, this is caused by several underlying factors. In deciding a case, a judge must be objective in deciding the case he is proceeding over so that the public's trust in the law remains pure without intervention by any party. This research aims to determine the factors that underlie disparities in criminal cases as well as efforts to overcome the disparity phenomenon. This research uses normative legal research methods and to analyze using qualitative descriptive analysis. The research results show several factors including: 1) Background, 2) Facts of the Trial, 3) Requisition or Prosecutor's Demands and 4) Mens Rea or a person's inner intention in committing a crime. Meanwhile, efforts to overcome this phenomenon include guidance provided by the Supreme Court to judges. Judges must also adhere firmly to the law on judicial power and pay attention to Article 54 of Law No. 1 of 2023 concerning the Criminal Code (KUHP). and supervision is carried out so that the judge in leading a trial process does not have interference from any party who is not responsible.